Oracle 11g : - Casteel, Joan (Course Technology/Cengage Learning, 2010)
ORACLE 11G: SQL is not simply a study guide; it is written for individuals who have just a basic knowledge of databases and can be utilized in a course on this latest implementation of SQL from Oracle.